2016
DOI: 10.1111/ijpo.12126
|View full text |Cite
|
Sign up to set email alerts
|

School beverage environment and children's energy expenditure associated with physical education class: an agent‐based model simulation

Abstract: Sugar-sweetened beverage vending machines in school may offset some of the EE in PE classes. This could be avoided if water is the only readily available source for children's fluid replacement after class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The selection of sugarsweetened, flavoured and marketed sports drinks over healthier beverages may attenuate the beneficial effect of physical activity as shown in our study. In line with our results, a simulation study by Chen et al also showed that sugar-sweetened beverage vending machines in schools may offset some of the benefits of increased energy expenditure in physical education classes (39). This study simulated the behaviour of 13-year-old children in a physical education class with nearby water fountains and found that adding sugar-sweetened beverage vending machines could offset physical education energy expenditure by as much as 90 kcal per child.…”
Section: Discussionsupporting
confidence: 88%
“…The selection of sugarsweetened, flavoured and marketed sports drinks over healthier beverages may attenuate the beneficial effect of physical activity as shown in our study. In line with our results, a simulation study by Chen et al also showed that sugar-sweetened beverage vending machines in schools may offset some of the benefits of increased energy expenditure in physical education classes (39). This study simulated the behaviour of 13-year-old children in a physical education class with nearby water fountains and found that adding sugar-sweetened beverage vending machines could offset physical education energy expenditure by as much as 90 kcal per child.…”
Section: Discussionsupporting
confidence: 88%
“…Agent‐based models more often used a time horizon of 5 years or less (median 3 years), while time horizons used in the system dynamics models were more variable (median 25 years), eg, four models used 5 years or less, two models used 15 to 20 years, and three models used 45 to 50 years. The model with the smallest time horizon of 30 to 60 minutes examined behavior of children in the confines of a physical education class. The model that was run for 2.5 generations examined effects of school quality policies and built environment on disparities in body mass index (BMI) between US Black and White populations …”
Section: Resultsmentioning
confidence: 99%
“…Several models (n = 7) also included interactions between individuals and their immediate food and physical activity environments , all using agent‐based modeling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a large extent, younger children depend on the accessibility of foods at home and screen time is generally a home activity that is bound by family rules [33]. With increasing age, children spend more unsupervised time with their friends [9] and they often receive pocket money that is frequently spent on soft drinks and fast food [34,35] outside the home environment [36]. Family members are more alike in the intake of healthy In model 1e the age difference between the sibling is ≤2.7 years.…”
Section: Discussionmentioning
confidence: 99%